The value of contrast-enhanced ultrasound in assessing carotid plaque vulnerability and predicting stroke risk - Junjie Cao; Yuqi Zeng; Yang Zhou; Zhichao Yao; Ziyi Tan; Guijun Huo; Lili Zhang; Dayong Zhou (Scientific Reports)
Abstract The presence of vulnerable carotid plaques plays a critical role in ischemic stroke pathogenesis, with intraplaque neovascularization (IPN) serving as a key indicator of plaque instability. Contrast-enhanced ultrasound (CEUS) provides a comprehensive evaluation of both plaque surface morphology and microvascular features. This study assesses the utility of CEUS in identifying vulnerable carotid plaques, quantifying IPN, and predicting stroke risk. The study involved 91 patients with carotid stenosis who underwent carotid endarterectomy (CEA). Preoperative assessments included CEUS and high-resolution magnetic resonance imaging (HR-MRI). Following surgery, plaque samples were collected and subjected to pathological analysis. CEUS offered comprehensive morphological insights, categorizing plaques by the direction of diffusion into inside-out and non-inside-out types. Neovascularization was semi-quantitatively evaluated using CEUS. HR-MRI and pathological assessments identified the composition and vulnerability of plaques. Microvessel density (MVD), microvessel area (MVA), and microvessel ratio (MVR) in plaque sections were quantified using high-power microscopy. Among the 91 subjects, 53 had a history of symptomatic stroke, while 38 had experienced asymptomatic stroke events. The analysis identified a significant association between symptomatic stroke events and fibrous cap rupture (FCR), as indicated by CEUS (P = 0.032), contrast agent diffusion within the plaque (P = 0.002), and a semi-quantitative grade 3 neovascularization (P = 0.007). Regression analysis further established CEUS grade 3 as an independent predictor of symptomatic stroke events (OR = 3.39, 95% CI: 1.25–9.19). CEUS showed comparable sensitivity, specificity, positive predictive value, negative predictive value, and overall accuracy in identifying vulnerable plaques when compared to HR-MRI, with slightly superior values for CEUS; however, the differences did not reach statistical significance (P = 0.503). Plaques demonstrating inside-out contrast agent diffusion had a markedly higher incidence of FCR and intraplaque hemorrhage (IPH) than those without such diffusion (P < 0.001). A positive correlation existed between the CEUS grade and both MVD and MVR (P < 0.001), but no significant relationship was observed with MVA (P = 0.221). Additionally, a significant association was found between the CEUS grade and IPH (P = 0.008). In summary, this study emphasizes the utility of CEUS in identifying vulnerable carotid plaques and evaluating neovascularization, both of which correlate with stroke risk. Notably, a CEUS grade 3 score may serve as an independent predictor of symptomatic stroke. This evidence supports the potential of CEUS as an effective, non-invasive method for assessing carotid plaque instability and identifying individuals at elevated risk for stroke.